2017
DOI: 10.1371/journal.pntd.0005866
|View full text |Cite
|
Sign up to set email alerts
|

Updated estimation of the impact of a Japanese encephalitis immunization program with live, attenuated SA 14-14-2 vaccine in Nepal

Abstract: BackgroundJapanese encephalitis (JE) is a mosquito-borne disease that is associated with considerable morbidity and mortality in many Asian countries. The objective of this study was to describe the impact of the JE immunization program using SA 14-14-2 JE vaccine implemented in Nepal during 2006 through 2011. A previous assessment after the initial program implementation phase described a significantly lower post-campaign JE incidence compared to expected incidence; however, the previous evaluation had limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…[8][9][10][11][12] Like other successful flavivirus vaccines against yellow fever and Japanese encephalitis, the majority of dengue vaccine candidates either approved for limited license or in Phase III trials are LAVs. 8,[13][14][15] These require shipment in lyophilized form at 4 C and must be reconstituted immediately before use to avoid loss in potency. 16,17 Therefore, systems enabling the preservation of DENV viability in dry formulation and at ambient temperatures will be essential for the development of LAVs that can be delivered and administered under CTC conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12] Like other successful flavivirus vaccines against yellow fever and Japanese encephalitis, the majority of dengue vaccine candidates either approved for limited license or in Phase III trials are LAVs. 8,[13][14][15] These require shipment in lyophilized form at 4 C and must be reconstituted immediately before use to avoid loss in potency. 16,17 Therefore, systems enabling the preservation of DENV viability in dry formulation and at ambient temperatures will be essential for the development of LAVs that can be delivered and administered under CTC conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This is partly due to the complexity of dengue epidemiology, population immunity, and the interplay between viral pathogenesis and host immunological mechanisms . Like other successful flavivirus vaccines against yellow fever and Japanese encephalitis, the majority of dengue vaccine candidates either approved for limited license or in Phase III trials are LAVs . These require shipment in lyophilized form at 4 °C and must be reconstituted immediately before use to avoid loss in potency .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the context of limited evidence regarding the effectiveness of vector control, bed nets, swine immunization or animal sequestration ( Igarashi, 2002 ), WHO recommends that countries achieve and maintain high human vaccine coverage to realize the greatest reductions in the number of human JE cases ( WHO, 2016 ). Studies conducted in other JE-endemic Asian countries have reported human immunization is effective in terms of decreasing AMES burden and health care costs ( Touch et al, 2010 , Upreti et al, 2017 , Yin et al, 2012 ). Immunization strategies including but not limited to introduction of JE vaccine into the routine childhood immunization program, mass vaccination of children under 15 years of age, and mass vaccination in limited geographic areas need to be examined, considering the cost-effectiveness ratio of the approach and potential for substantially decreasing disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…Although pre-existent JEV antibodies due to JEV vaccination has shown to potentiate DENV infection in vitro and although our data suggest that those who had received the JEV vaccine (and therefore had JEV-specific IgG antibodies) were more likely to have severe dengue, these data should be further validated by carrying out careful prospective studies in the communities where these viruses co-circulate. Given that the JEV vaccine has significantly reduced mortality and morbidity of encephalitis due to JEV throughout the world including Sri Lanka [ 27 , 32 , 33 ], it would be important to carefully examine such associations in other JEV and DENV endemic countries before concluding that JEV increases dengue disease severity.…”
Section: Discussionmentioning
confidence: 99%